Tax Revenue and Economic Growth: Empirical Evidence from Nigeria - Ifeoma Osamor; Godwin Omoregbee; Fadekemi Ajasa-Adeoye; Josephine Olumuyiwa-Loko (Journal of Economics and Behavioral Studies, 2023)
Organizations reduced their tax revenue through tax evasion and avoidance, thereby affecting the economic growth of the country. In an attempt to further stress this assertion, this study aims to empirically examine the effects of tax revenue on economic growth in Nigeria. Tax revenue was a proxy with PPT, CIT, VAT and CTD, while economic growth was proxy with GDP. Ex post facto research design was employed, while time series quarterly data were collected from the statistical bulletins of CBN and FIRS for 10 years (2011-2020). Data collated were analyzed using descriptive analysis, unit root test, bounds cointegration test and ARDL. The findings revealed that PPT, CIT, VAT and CTD had positive insignificant effects on economic growth. The study concluded that tax revenue had insignificant effects on the economic growth of Nigeria and therefore, recommended that proper tax audit should constantly be carried out to reduce tax evasion and avoidance.